(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Public Health Scotland published Physical Activity Referral Standards in 2022. These aim to enhance physical activity referral scheme (PARS) quality, reduce variability in design and delivery, and build evidence of what works. This novel study evaluates the implementation of data collection recommendations made in national PARS policy. Methods: This quantitative study included: 1) a national online survey mapping the design and delivery of PARS, and 2) the collation of anonymised routinely collected service data from PARS providers in Scotland. Descriptive data for part one, and data quality, uptake, and adherence for part two were analysed using R. Results: Thirty-two PARS provider organisations representing 28/32 local government areas in Scotland completed the survey. Twenty-six (84.4%) PARS included explicit behaviour change and supervised activity and/or signposting to activities. The majority of providers were leisure trusts (53%, n = 17). A wide range of medical conditions were accepted from referrals via primary (n = 32, 100%), and secondary (n = 29, 90.6%) care. Fourteen PARS (43.8%) allowed self-referrals. PARS offered multiple activities, with the most common being specialist classes (n = 28, 90.6%) and gym-based sessions (n = 27, 84.4%). Twenty-three (71.9%) providers received some external funding and nine (28.1%) expected participants to pay to attend. PARS duration varied from 8–52 weeks and 11 schemes (34.4%) were open ended. Seventeen schemes expressed interest in providing anonymised service data, but some were unable to extract data from their systems. Data for 21,956 individuals were collated from 10 PARS. No PARS collected all data fields suggested within the standards. Where collected, data field completion was highest for demographics of referrals (e.g. age, 85.3–100% available, gender, 98.6–99.8% available) and reason for referral (89.4–99.9% available). Data field completion for recording uptake varied from 43.5–100% of all referrals, and recording of attendance/adherence varied from 18.5–100% of those who started. Uptake of PARS varied from 38.6–59.7% and adherence of those who started from 14.1–68.9%, but these figures may partially reflect poor data field completion. Conclusions: PARS in Scotland require support to improve routine data collection and to enable data extraction for analysis. Future analysis of routine data combined with scheme characteristics can increase understanding of what works. Support/Funding Source: Chief Scientist Office, Scotland [HIPS/22/10]. Keywords: Public health, evaluation study, health policy, exercise, physical activity referral